IT Workplace Preferences, Job Demands, and Work Exhaustion. Issue 6 (2nd November 2022) - Bui, Son; Le-Nguyen, Khuong; "Neo" Bui, Quang; Jacks, Tim; Palvia, Prashant
ABSTRACT: Work exhaustion has become one of the main job stressors that leads to dissatisfaction and worker turnover. To retain IT talent, managers seek ways to reduce stress, such as lowering workload or increasing monetary compensation. In this paper, we explore work exhaustion in a developing country to examine antecedents and mitigating factors for work exhaustion. Using a survey of 289 IT professionals in Vietnam, a developing country with high turnover rates and limited IT resources devoted to talent retention, we test how job demands and workplace preferences impact work exhaustion. The findings show that a preference for strong workplace structure suppresses workers' perceptions of work overload and work/home conflict. Additionally, preference for strong workplace autonomy surprisingly amplifies perceived work overload and has no impact on work/home conflict. Our findings suggest the importance of workplace characteristics as well as IT occupational culture in mitigating work exhaustion for IT employees.